An attempt to reconstruct selected elements the original site topography of the Teutonic castles at Unisław and Starogród (Chełmno Land, Northern Poland) based on archaeological and cartographic data - Molewski, Paweł; Wasik, Bogusz; Wiewióra, Marcin (Bulletin of Geography. Physical Geography Series, 2018)
The article presents an attempt to reconstruct the original site topographies of 13th-century Teutonic castles at Unisław and Starogród, which have not been preserved in the surface terrain. Both castles are situated in the west of Chełmno Land on the edge of a moraine plateau 30 to 50 metres above the floor of the Vistula valley. The reconstruction used a research approach known as Historical GIS (HGIS), which, besides archaeological data, employs digitised historical cartographic sources. The research showed that changes in the original site topography are associated with anthropogenic transformations in the plateau surface, mainly due to agricultural use, and retreat of the plateau edge resulting from natural and man-made landslide processes. The authors believe that the reconstruction of the castles’ original site topographies could be used to verify detailed hypotheses related to the conditions of their construction and operation.